Cleavage of a C–C σ bond between two phenyl groups under mild conditions during the construction of Zn(ii) organic frameworks. Issue 20 (27th September 2016) - Liu, Bo; Zhou, Hui-Fang; Guan, Zheng-Hui; Hou, Lei; Cui, Bin; Wang, Yao-Yu
Abstract : In this paper, we present a simple and effective strategy to cleave the C(sp 2 )–C(sp 2 ) σ bond between two phenyl groups under mild conditions during the construction of Zn(ii ) organic frameworks. Abstract : Due to the high bond dissociation energy, low proton acidity, and highly nonpolar character of the C–C bond, activation or cleavage of the bonds, especially the C(sp 2 )–C(sp 2 ) σ bond, is one of the most challenging tasks in synthetic chemistry. Herein, we present a simple and effective strategy for cleavage of the C(sp 2 )–C(sp 2 ) σ bond between two phenyl groups under mild reaction conditions during the construction of zinc(ii ) organic frameworks. By reacting the organic ligand 3-(2′, 5′-dicarboxyphenyl)benzoic acid (H3 dbba) and 1, 2-bis(4-pyridyl)ethane (bpe) with Zn(ii ) ions in dimethylformamide, dimethylacetamide, or diethylformamide solvent systems, complete cleavage of the C(sp 2 )–C(sp 2 ) σ bonds between two phenyl groups occurred and all H3 dbba ligands were broken into 1, 4-benzenedicarboxylate (bdc) and benzoic acid, and a new coordination polymer, [Zn(bdc)(bpe)] was obtained. We discuss a plausible mechanism for this cleavage mode and confirm that it occurred. This extraordinary example of C(sp 2 )–C(sp 2 ) σ bond cleavage under mild conditions provides new insights for both organic and inorganic synthetic chemistry.